Swat : An Afghan Society in Pakistan : Urbanisation and Change in Tribal Environment - Inam-ur-Rahim and Viaro, Alain M. (Karachi City Press, 2002)
Extrait de la couverture : "The Pukhtun society of the Swat valley in the North West Frontier Province, Pakistan, is at the crossroads of social transformation and change. The Mghan Yusafzai tribe, which migrated from Kabul more than five hundred years ago and settled in the Swat valley, has retained its particular tribal culture and characteristics to this day. It was during the last century that the culture of Yusufzai Pukhtuns, residing on this side of the Durand Line, began to be influenced by the regional historical and geo-political forces. From a rural tribal society, governed by the centuries old tribal code - Pukhtunwali - the Pukhtuns have been gradually urbanising, responding to the emerging socio-economic and historical changes. The transformation is not without its ramifications - social conflicts, breakdown of old tribal social structures and values, unplanned economic growth and its adverse effects on the natural resource base of the lush green valley, often compared with Switzerland for its scenic beauty. This book chronicles the process of urbanisation and change in the broader context, embracing the history, geography, agriculture and economics, demography and migration, culture and politics of the Swat valley. It analyses the impact of abolition of the traditional Wesh system of land distribution, merger of the State of Swat within the nation-state of Pakistan, the increasing influence of religious groups subsequent to the Soviet occupation of Afghanistan and the advent and decline of the Taliban, the remittance economy and tourism, and the donor-funded development projects that have a bearing on the process of urbanisation. What emerges is an insightful picture of the contemporary Swat valley, leading to a better understanding of the complex forces that are transforming its tribal Pukhtun society."
Keywords: Pushtuns -- Pakistan -- Pakistan--Swāt District